Learning and memory associated with aggression in Drosophila melanogaster - Yurkovic, Alexandra (National Academy of Sciences, 2006)
Male Drosophila melanogaster (Canton-S strain) exhibit aggression in competition for resources, to defend territory, and for access to mates. In the study reported here, we asked: (i) how long flies fight; (ii) whether flies adopt distinct winning and losing strategies as hierarchical relationships are established; (iii) whether flies exhibit experience-dependent changes in fighting strategies in later fights; and (iv) whether flies fight differently in second fights against familiar or unfamiliar opponents. The results showed that flies fought for up to 5 h. As hierarchical relationships were established, behavioral strategies changed: winners progressively lunged more and retreated less, whereas losers progressively lunged less and retreated more. Encounters between flies were frequent during the first 10 min of pairing and then dropped significantly. To ask whether flies remembered previous fights, they were re-paired with familiar or unfamiliar opponents after 30 min of separation. In familiar pairings, there were fewer encounters during the first 10 min of fighting than in unfamiliar pairings, and former losers fought differently against familiar winners than unfamiliar winners. Former losers lost or no decision was reached in all second fights in pairings with familiar or unfamiliar winners or with naive flies. Winner/winner, loser/loser, and naive/naive pairings revealed that losers used low-intensity strategies in later fights and were unlikely to form new hierarchical relationships, compared with winners or socially naive flies. These results strongly support the idea that learning and memory accompany the changes in social status that result from fruit fly fights.